Identification of putative monolignol transporter gene homolog I in Oryza sativa - Othman, Shuhaidah (2015)
Lignin is present in plant’s cell wall constitutes which mainly function to provide vital structural support to the plant. The transportation of lignin precursors, monolignols, from the membrane to the cell wall, where they are oxidized and polymerized, is facilitated by ATP dependent transport process. This process involves ATP binding cassette like transporters, namely monolignol transporter. Studies have been conducted using Arabidopsis thaliana as an experimental model to prove this idea. Hence, this project was performed using Oryza sativa (cultivar MR219) to identify putative monolignol transporters based on sequence identity detection of a target gene from these two organisms. The putative target gene sequences that possessed a high identity with AtABCG29 gene was obtained from the BLAST program (NCBI) and subjected to a specific primer designing step. A number of primer sets were designed to amplify fragment by fragment in isolating the whole sequence of the putative target gene, which is approximately 4.7 kb in length. Total RNA was extracted from four weeks old seedlings of O. sativa followed by the synthesis of cDNA and polymerase chain reaction to amplify the target gene by using the specifically designed primers. A housekeeping gene (Actin11) was used as a positive control in this study. Final results showed that out of eleven primer pairs designed, four of them produced a significant single band at expected size. Thus, it can be concluded that the putative target gene in O. sativa has a relatively high sequence homology with AtABCG29 from Arabidopsis.